The Values of Character in Traditional Games Simalungun Society - Ramlan Damanik; Warisman Sinaga (Budapest International Research and Critics University, 2021)
Simalungun ethnic is one of the ethnic in North Sumatra, Simalungun ethnic have some traditional games, marlubuk,marsitengka, marjalengkat, batu marsiada (mardara), marultop, margala, margodok, pattik lele, pecah piring, olei,olei, margasing, jalengkat sarip, marjakop, dan marampera. Discussions with an informan and immediately held a game involve some children in Sirpang Sigodang Kecamatan Raya village, for get Simalungun traditional games’ type. Methods such as recording, documenting, interviewing have eighteen character values, among others: religious values, honesty, tolerance, discipline, hard work, creative thinking, independence / independence, democracy, curiosity, national spirit, patriotism, appreciation for achievement, hospitality, peace, love to read, protect the environment, social care, and responsibility. Simalungun traditional games can be played at school, some friends in neighborhood for form character values.